Restoring fiscal sanity, 2005 : meeting the long-run challenge - Rivlin, Alice M.; Sawhill, Isabel V. (Brookings Institution Press, 2005)
"Policy experts address how to bring federal spending and revenue in line over the next decade and into balance over the longer term, focusing on reforms in the tax system, Social Security, and Medicare"--Provided by publisher